Paul Maenz Köln 1970-1980 : Der Blick zurück ist ein Blick auf die Gegenwart und - oder die Wahrheit hat viele Brüste. - Galerie Paul Maenz, Köln; Ammann, Jean-Christophe; Celant, Germano; Faust, Wolfgang Max (Köln : Galerie Paul Maenz, 1981)
Anselmo, Giovanni ; Art & Language ; Barry, Robert ; Boetti, Alighiero ; Buren, Daniel ; Chia, Sandro ; Clemente, Francesco ; Cucchi, Enzo ; Darboven, Hanne ; Fabro, Luciano ; Feldmann, Hans-Peter ; Haacke, Hans ; Kiefer, Anselm ; Kosuth, Joseph ; Kounellis, Jannis ; Mariani, Carlo Maria ; Paladino, Mimmo ; Paolini, Giulio ; Penone, Giuseppe ; Poirier, Anne & Patrick ; Roehr, Peter ; Rutault, Claude ; Salvo ; Toroni, Niele
Publikationen p. 93-100
Duits
boek